2011
DOI: 10.1007/s00104-010-2043-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimaler Zeitpunkt zur prothetischen Versorgung von Schenkelhalsfrakturen

Abstract: The lower postoperative inflammatory reaction after early surgery of hip fractures provides a better outcome when treated with arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Therefore, most surgeons refer to temporal patterns rather than the value at a specific time point [ 18 ]. Several studies have investigated CRP kinetics following surgical procedures [ 22 26 ]. These studies consistently found that CRP increases after the surgery, peaks on the second day, and then gradually returns to normal around the seventh day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most surgeons refer to temporal patterns rather than the value at a specific time point [ 18 ]. Several studies have investigated CRP kinetics following surgical procedures [ 22 26 ]. These studies consistently found that CRP increases after the surgery, peaks on the second day, and then gradually returns to normal around the seventh day.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results show that already on day 1 and 2 a differentiation of the markers between PT+Inf and PT-Inf occurs, which in these cases suggests an early enhanced immune response in the PT+Inf group. It was shown before that primary trauma injury triggers an immunomodulatory response that is associated with an increase in CRP (34). Interleukins play a particularly prominent role in the development of posttraumatic complications und and have been widely studied in relation to trauma (15,16,35).…”
Section: Early Tracking Of Posttraumatic Infection By Biomarkers Is Efficientmentioning
confidence: 99%
“…Neumaier et al [12] reported that the C-reactive protein (CRP) values were significantly lower in early surgery within 24 h after trauma than in delayed surgery. Moreover, they found that a lower postoperative inflammatory reaction after early surgery of hip fractures provides a better outcome when treated with arthroplasty.…”
Section: Discussionmentioning
confidence: 99%